Safety and Efficacy of Biweekly Gemcitabine in Combination with Capecitabine in Elderly and Frail Patients with Resected Pancreatic Cancer - Muhammad W. Saif, MD; Nausheen Hakim, MD; Jeffrey Chi, MD; Hasan Rehman, MD; William Nealon; Antonia Maloney; Melissa H. Smith (Pancreas, 2025)
Background The European Study Group for Pancreatic Cancer (ESPAC-4) study showed that gemcitabine and capecitabine (GemCap) con-ferred a survival benefit over gemcitabine monotherapy in resected pancreatic cancer (PC) patients. ESPAC-4 included patients with a median age of 65-years (37-81) and Eastern Cooperative Oncology Group (ECOG) performance status (PS) of 0,1 in 97%. We present our experience with an adopted biweekly regimen of GemCap in patients who were ≥75-years old and deemed not suitable for the ESPAC-4 regimen. MethodsPatients received a biweekly regimen of GemCap (gemcitabine 1000 mg/m2 every 2-weeks and capecitabine 1000 mg/m2 twice a day orally on days 1-7 every 2-weeks). Patients were evaluated for progression-free survival (PFS), overall survival (OS), and sites of recurrence. Toxicities were graded according to National Cancer Institute (NCI) common terminology criteria for adverse events (CTCAE) v5.0.ResultsThirty-five (35) patients with a median age of 79-years were treated with biweekly GemCap adjuvant treatment. Seventy-two percent (72%) of patients had ECOG PS of 2. The median PFS and OS were 8-months and 22-months. Twenty-five percent (25%) had local recurrence, 60% had metastatic disease and 8.6% had no evidence of disease (NED). The most frequent toxici-ties were grades 1-2 anemia (20%), thrombocytopenia (8%), and hand-foot syndrome (HFS) (10%). Grade ≥3 included diarrhea (4%) and HFS (1%). Conclusion Our study showed that biweekly gemcitabine in combination with capecitabine can be an acceptable regimen with efficacy com-parable to historical control and a favorable toxicity profile in elderly and frail patients. Patients on this regimen also make fewer visits to the oncologist. A biweekly GemCap regimen warrants further exploration in patients not suitable for FOLFIRINOX (a combination of bolus and infusional fluorouracil, leucovorin, irinotecan and oxaliplatin), full-dose GemCap, or a clinical trial.